Low‐dose aspirin and risk of gastric and oesophageal cancer: A population‐based study in the United Kingdom using The Health Improvement Network - García Rodríguez, Luis A. (Int J Cancer, 2020)
There is increasing interest regarding potential protective effects of low‐dose aspirin against various gastrointestinal cancers. We aimed to quantify the association between use of low‐dose aspirin and risk of gastric/oesophageal cancer using a population‐based primary care database in the UK. Between January 2005 and December 2015, we identified a cohort of 223 640 new users of low‐dose aspirin (75‐300 mg/day) and a matched cohort of nonusers at the start of follow‐up from The Health Improvement Network. Cohorts were followed to identify incident cases of gastric/oesophageal cancer. Nested case‐control analyses were conducted and adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were calculated for current vs nonuse of low‐dose aspirin using logistic regression. Current use was defined as when low‐dose aspirin lasted 0 to 90 days before the index date (event date for cases, random date for controls) and previous duration was ≥1 year. We identified 727 incident cases of gastric cancer and 1394 incident cases of oesophageal cancer. ORs (95% CIs) were 0.46 (0.38‐0.57) for gastric cancer and 0.59 (0.51‐0.69) for oesophageal cancer. The effect remained consistent with no clear change seen between previous duration of low‐dose aspirin use of 1‐3, 3‐5 or >5 years. The reduced risks was seen with 75 mg/day, and effects were consistent in lag‐time analyses. In conclusion, our results indicate that use of low‐dose aspirin is associated with a 54% reduced risk of gastric cancer and a 41% reduced risk of oesophageal cancer as supported by mechanistic data.